Renal denervation in comparison with intensified pharmacotherapy in true resistant hypertension: 2-year outcomes of randomized PRAGUE-15 study - Rosa, Ján; Widimský, Petr; Waldauf, Petr; Zelinka, Tomáš; Petrák, Ondřej; Táborský, Miloš; Branny, Marian; Toušek, Petr; Čurila, Karol; Lambert, Lukáš; Bednář, František; Holaj, Robert; et al. (Journal of hypertension, 2017)
OBJECTIVES: The randomized, multicentre study compared the efficacy of renal denervation (RDN) versus spironolactone addition in patients with true resistant hypertension. We present the 24-month data. METHODS: A total of 106 patients with true resistant hypertension were enrolled in this study: 52 patients were randomized to RDN and 54 patients to the spironolactone addition, with baseline SBP of 159 ± 17 and 155 ± 17 mmHg and average number of drugs 5.1 and 5.4, respectively. Two-year data are available in 86 patients. Spironolactone addition, as crossover after 1 year, was performed in 23 patients after RDN, and spironolactone addition followed by RDN was performed in five patients. RESULTS: Similar and comparable reduction of 24-h SBP after RDN or spironolactone addition after randomization was observed, 9.1 mmHg (P = 0.001) and 10.9 mmHg (P = 0.001), respectively. Similar decrease of office blood pressure (BP) was observed, 17.7 mmHg (P < 0.001) versus 14.1 mmHg (P < 0.001), whereas the number of antihypertensive drugs did not differ significantly between groups. Crossover analysis showed nonsignificantly better efficacy of spironolactone addition in 24-h SBP and office SBP reduction than RDN (3.7 mmHg, P = 0.27 and 4.6 mmHg, P = 0.28 in favour of spironolactone addition, respectively). Meanwhile, the number of antihypertensive drugs was significantly increased after spironolactone addition (+0.7, P = 0.001). CONCLUSION: In the settings of true resistant hypertension, spironolactone addition (if tolerated) seems to be of better efficacy than RDN in BP reduction over a period of 24 months. However, by contrast to the 12-month results, BP changes were not significantly greater.
Keywords: dospělí; Kidney; Mineralocorticoid Receptor Antagonists; hypertenze; Female; klinické křížové studie; Adult; výsledek terapie; ženské pohlaví; Coronary Vasospasm; lidé; Sympathectomy; Drug Therapy, Combination; Blood Pressure Monitoring, Ambulatory; Treatment Outcome; Cross-Over Studies; následné studie; krevní tlak; koronární vazospasmus; prospektivní studie; sympatektomie; Follow-Up Studies; Hypertension; Male; Aged; Prospective Studies; kombinovaná farmakoterapie; ambulantní monitorování krevního tlaku; lidé středního věku; Antihypertensive Agents; senioři; mužské pohlaví; antihypertenziva; Blood Pressure; ledviny; Spironolactone; spironolakton; Middle Aged; antagonisté mineralokortikoidních receptorů; Humans